Mucoadhesive compositions and methods of use thereof
By using hydrophobically modified polymeric adhesive active substances in the mucosal adhesive composition, a stable interpenetrating network is formed, and the problems of poor shelf life stability and insufficient adhesion and retention time in the prior art are solved, and stronger adhesion and retention, better buffering effect and longer shelf life are achieved.
Patent Information
- Application Number
- CN202080075478.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-08-26
- Filing Date
- 2020-08-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-08-24
AI Technical Summary
The existing mucosal adhesion compositions have poor shelf life stability and insufficient adhesion holding time and strength during use, resulting in a gap between the denture and the gums not being sealed, affecting the comfort of use and oral health.
By incorporating hydrophobically modified polymeric adhesive active substances into the mucosal adhesive composition, an interpenetrating network of slightly water-soluble, water-dispersible or water-insoluble interpenetrating network is formed, thereby enhancing the cohesion and stability of the adhesive.
It significantly improves the strength and duration of adhesion retention, enhances the cushioning effect between the gum and denture, improves the gap sealing, extends the shelf life, and improves the ease of cleaning after use.
Smart Images

Figure CN114630656B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a mucoadhesive composition, and more particularly, to a mucoadhesive composition comprising a denture adhesive composition, wherein the denture adhesive composition comprises (i) a maleic acid copolymer, or a maleic anhydride copolymer, or a salt of a maleic acid copolymer or a maleic anhydride copolymer; (ii) a cellulose ether; (iii) a cross-linked polyvinyl pyrrolidone polymer that is swellable but insoluble in water; and (iv) a hydrophobic oil or a hydrophilic non-oil component as a carrier. Background Art
[0002] Mucoadhesive compositions, including denture adhesive preparations, are generally available in the form of pastes, powders or extruded dry sheets / dry films, and are used to provide users of partial or full dentures with a means of firmly retaining artificial dentures in the oral cavity, or to deliver therapeutically active substances to desired areas within the oral cavity by topical application. Typically, mucoadhesive compositions, including denture adhesive pastes, consist of water-soluble or water-swellable adhesive polymers suspended in an orally acceptable carrier matrix, which is generally composed of different proportions of long-chain hydrocarbons or long-chain fatty acids such as mineral oil, vegetable oil, petrolatum, etc. During use, the adhesive component in the mucoadhesive composition (particularly the denture adhesive paste) is activated when in contact with saliva, causing the denture adhesive preparation applied between the gums and the denture to hydrate, swell, and subsequently form an adhesive and cohesive retention. The duration and strength of the adhesive retention provided by the denture adhesive preparation are the main quantitative performance parameters of the denture adhesive. Other semi-quantitative or quantitative parameters used to define the overall performance characteristics of the denture adhesive formulation may include film thickness and the cushioning effect provided by the denture adhesive between the gum and the denture, preventing food particles from entering the interstitial space between the gum and the denture by providing excellent interstitial sealing, and preventing the loss of denture adhesive material between the gum and the denture due to seepage during use. Since conventional mucoadhesive compositions including denture adhesive pastes are essentially suspensions or powders of solid active ingredients in a semi-solid or liquid matrix containing various types of oils, the shelf stability of the formulation is lost due to syneresis and separation of the carrier matrix, and the solid active ingredients may also adversely affect the adhesive performance.
[0003] Therefore, an ideal mucoadhesive composition (particularly a denture adhesive paste) should have suitable shelf-life stability over a sustained period of time, provide sufficiently high instant dry adhesion and prolonged adhesion retention during use, provide sufficient cushioning between the gums and the dentures to ensure comfortable use, be able to seal the gap between the dentures and the gums to prevent food particles from entering the gap, reduce oral discomfort caused by leakage of partially hydrated denture adhesive between the gums and the dentures, and be easy to clean after use.
[0004] US Patent 3,440,065A describes the use of sodium salt of carboxymethylcellulose (sodium CMC) as an active adhesive ingredient in denture adhesive formulations.
[0005] US Patent No. 4,514,528A describes the use of partial sodium / calcium mixed salts of lower alkyl vinyl ether-maleic anhydride copolymers (more specifically methyl vinyl ether-maleic anhydride copolymers) as adhesive actives in denture adhesive formulations.
[0006] U.S. Patent No. 4,569,955 A describes a combination of sodium CMC and the Ca / Na salt of a copolymer of lower alkyl vinyl ether-maleic anhydride (particularly methyl vinyl ether-maleic anhydride) in a denture adhesive formulation. Since then, a class of synthetic copolymers of lower alkyl vinyl ethers (most commonly methyl vinyl ether) and maleic anhydride, metal salts of these polymers, or metal cross-linked forms of these polymers, or mixtures of these polymers with different types of water-soluble cellulosic materials (most commonly, but not limited to sodium CMC) have been used in oil-based denture adhesive formulations.
[0007] DE 32 28 335 A1 discloses the use of polyvinylpyrrolidone (PVP) as an adhesive active substance for denture adhesive preparations.
[0008] EP2620136B1 and US9408780B2 describe the use of PVP in denture adhesive formulations for the following purposes: to increase the initial dry adhesion of oil-based denture adhesive formulations, as an adhesive active substance for oil-free denture adhesive formulations, as a formulation and stabilization aid, and as a hydration promoter for oil-based denture adhesive formulations.
[0009] Although hydration of adhesive actives in contact with saliva during use is critical to activating and establishing the adhesive properties of mucoadhesive compositions, particularly denture adhesives, the rate and extent of hydration of adhesive actives is critical to the overall performance of mucoadhesive compositions, particularly denture adhesive formulations. Adhesive actives such as Ca / Na salts of copolymers of lower alkyl vinyl ether-maleic anhydride (particularly methyl vinyl ether-maleic anhydride), water-soluble celluloses such as CMC, and lactam polymers such as PVP hydrates dissolve in saliva during use. The loss of dissolved adhesive actives from between the gums and dentures in the form of "seepage" can adversely affect adhesive retention, cushioning, food sealing, and result in an unpleasant mouth feel.
[0010] The present application describes qualitative and quantitative improvements in the overall performance characteristics of mucoadhesive compositions, particularly denture adhesive compositions, achieved by incorporating hydrophobically modified polymeric adhesive actives into oil-based and oil-free mucoadhesive compositions, including denture adhesive formulations. The hydrophobic modification ranges from light substitution of short-chain hydrophobes to long-chain hydrophobes on the polymeric backbone to intra- and / or inter-light or heavy chain crosslinking of the polymeric backbone with hydrophobic crosslinkers, rendering the normally water-soluble polymeric adhesive actives slightly water-soluble, water-dispersible, or completely water-insoluble. At the same time, due to their analogous chemical structures and pendant groups similar to those of conventional polymeric adhesive actives, these hydrophobically modified polymers retain their inherent adhesive functionality in addition to functioning as cohesion builders by establishing water-insoluble but water-swellable interpenetrating networks in hydrated mucoadhesive compositions, including denture adhesive hydrogels. Incorporation of hydrophobically modified adhesive polymers as an additive or as a complete replacement for one or more adhesive actives in standard oil-based and oil-free mucoadhesive compositions, including denture adhesive formulations, demonstrates improved denture adhesive performance in terms of strength and duration of adhesive retention, film thickness and buffering effect, exudation control, shelf-life storage stability, and ease of cleaning compared to benchmark formulations. Summary of the invention
[0011] The main aspect of the present application is to provide an improved mucoadhesive composition comprising: (i) about 10% to about 75% by weight of a maleic acid copolymer or a maleic anhydride copolymer, or a salt of a maleic acid copolymer or a maleic anhydride copolymer; (ii) about 10% to about 50% by weight of at least one cellulose ether; (iii) about 0.1% to about 10% by weight of a swellable but water-insoluble cross-linked polyvinyl pyrrolidone polymer; and (iv) about 30% to about 70% by weight of an orally acceptable carrier.
[0012] One aspect of the present application provides a mucoadhesive oral composition comprising: (i) about 10% to about 75% by weight of a maleic acid copolymer or a maleic anhydride copolymer, or a salt of a maleic acid copolymer or a maleic anhydride copolymer; (ii) about 10% to about 50% by weight of at least one cellulose ether; (iii) about 0.1% to about 10% by weight of a swellable but water-insoluble cross-linked polyvinyl pyrrolidone polymer; and (iv) about 30% to about 70% by weight of an orally acceptable carrier; and (v) about 0.01% to about 20% by weight of an active ingredient selected from antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, sweeteners, and mixtures thereof, and further wherein the composition is in the form of a gel or liquid.
[0013] Another aspect of the present application provides a denture composition comprising: (i) about 10% to about 75% by weight of a maleic acid copolymer or a maleic anhydride copolymer, or a salt of a maleic acid copolymer or a maleic anhydride copolymer; (ii) about 10% to about 50% by weight of at least one cellulose ether; (iii) about 0.1% to about 10% by weight of a swellable but water-insoluble cross-linked polyvinyl pyrrolidone polymer; (iv) about 30% to about 70% by weight of an orally acceptable carrier; and (v) about 0.01% to about 20% by weight of an active ingredient selected from antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, sweeteners, and mixtures thereof, and further wherein the composition is in the form of a gel or liquid.
[0014] One aspect of the present application provides a mucoadhesive composition including a denture adhesive composition, wherein the maleic acid copolymer or maleic anhydride copolymer comprises maleic acid or maleic anhydride and C1-C4 alkyl vinyl ether, which has a predetermined weight average molecular weight of about 500,000 to 3,000,000, and is suitable for preparing a denture adhesive by: copolymerizing about 50 mol % of maleic anhydride and about 50 mol % of C1-C4 alkyl vinyl ether in a solvent or solvent-free process at about 50° C. to 150° C. in the presence of a free radical initiator to produce a uniform fine powder substantially free of residual maleic anhydride.
[0015] Another aspect of the present application provides a mucoadhesive composition comprising a denture adhesive composition, wherein the number average molecular weight of the methyl vinyl ether-maleic acid (MVE-MA) copolymer or the methyl vinyl ether-maleic anhydride (MVE-MA) copolymer is from about 50,000 to about 500,000, wherein about 50% by weight to about 100% by weight of the carboxyl units in the polymer are converted to a mixture of metal salts, wherein the metal can be selected from calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium and mixtures thereof.
[0016] Yet another aspect of the present application discloses a mucoadhesive composition comprising a denture adhesive composition, wherein a salt of an alkyl vinyl ether-maleic acid copolymer or a salt of an alkyl vinyl ether-maleic anhydride copolymer has a specific viscosity of 2.5 to 5.0 when measured as a 1 weight / volume % solution in a methyl ethyl ketone (MEK) solution at 25°C.
[0017] In another aspect, the present application discloses a mucoadhesive composition comprising a denture adhesive composition, the denture adhesive composition comprising: (i) about 15 wt % to about 70 wt % of a maleic acid copolymer selected from methyl vinyl ether-maleic acid (MVE-MA) copolymer or methyl vinyl ether-maleic anhydride (MVE-MA) copolymer or a salt thereof; about 10 wt % to about 50 wt % of carboxymethyl cellulose (CMC); about 0.1 wt % to about 10 wt % of a water-insoluble cross-linked polyvinyl pyrrolidone polymer; and about 10 wt % to about 60 wt % of an orally acceptable carrier.
[0018] Another aspect of the present application discloses a method for adhering a denture having a biological contact surface to the gums or roof of the mouth, the method comprising treating the biological contact surface of the denture with a mucoadhesive composition, particularly a denture adhesive composition, the denture adhesive composition comprising: (i) about 15% to about 70% by weight of a maleic acid copolymer selected from methyl vinyl ether-maleic acid (MVE-MA) copolymer or methyl vinyl ether-maleic anhydride (MVE-MA) copolymer or a salt thereof; (ii) about 10% to about 50% by weight of carboxymethyl cellulose; (iii) about 0.1% to about 10% by weight of a water-insoluble cross-linked polyvinyl pyrrolidone polymer; (iv) about 10% to about 60% by weight of an orally acceptable carrier; and (v) about 0.01% to about 20% by weight of an active ingredient selected from antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, sweeteners, and mixtures thereof, and further wherein the composition is a gel or a liquid. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Other embodiments of the present application can be understood through the accompanying drawings.
[0020] Figure 1-4 Shows the overlap of the average adhesion spectra of oil-based denture adhesive samples of Comparative Examples E1, E12-16.
[0021] Figure 5 The total adhesion force for each representative denture adhesive formulation is shown.
[0022] Figure 6 Represents the overlap of the average adhesion spectra of oil-free denture adhesive samples OF1 and OF2.
[0023] Figure 7 The total adhesion force for each representative oil-free denture adhesive formulation is shown.
[0024] Figure 8 The stability of selected oil-based denture adhesive formulations after 12 weeks at 45°C is shown. DETAILED DESCRIPTION
[0025] Before explaining in detail at least one aspect of the disclosed and / or claimed inventive concept, it should be understood that the disclosed and / or claimed inventive concept is not limited in its application to the construction and arrangement details of the components or steps or methods set forth in the following description or shown in the accompanying drawings. The disclosed and / or claimed inventive concept can have other aspects or can be practiced or performed in a variety of ways. In addition, it should be understood that the words and terms used herein are for descriptive purposes and should not be considered restrictive.
[0026] As used in accordance with the present disclosure, the following terms shall be understood to have the following meanings, unless otherwise indicated.
[0027] Unless otherwise defined herein, technical terms used in conjunction with the disclosed and / or claimed inventive concepts shall have the meanings commonly understood by those of ordinary skill in the art. In addition, unless otherwise required by context, singular terms shall include pluralities and plural terms shall include the singular.
[0028] The singular forms "a", "an", and "the" include the plural forms unless the context clearly dictates otherwise or is clearly implied to the contrary by the context of the reference. The terms "comprising" and "including" include more restrictive statements such as "consisting essentially of" and "consisting of.
[0029] For purposes of the following detailed description, except in any operating examples or where otherwise indicated, the numerical values expressing, for example, quantities of ingredients used in the specification and claims are to be understood as being modified in all instances by the term "about". The numerical parameters set forth in the specification and appended claims are approximations that may vary depending upon the desired properties to be obtained in practicing the present invention.
[0030] All percentages, parts, ratios and proportions used herein are by weight of the total composition, unless otherwise specified. All such weights as they pertain to listed ingredients are based on the active level and, therefore, do not include solvents or by-products that may be included in commercially available materials, unless otherwise specified.
[0031] All publications, articles, treatises, patents, patent disclosures, and other references cited herein are hereby incorporated in their entirety for all purposes to the extent consistent with the disclosure herein.
[0032] The use of the term "at least one" will be understood to include any number of one and more than one, including but not limited to 1, 2, 3, 4, 5, 10, 15, 20, 30, 40, 50, 100, etc. The term "at least one" can be extended to 100 or 1000 or more, depending on the term that follows it. In addition, the number of 100 / 1000 should not be regarded as limiting, as lower or higher limits may also produce satisfactory results.
[0033] As used herein, the words "comprising" (and any forms of comprising, such as "comprise" and "comprises"), "having" (and any forms of having, such as "have" and "has"), "including" (and any forms of including, such as "includes" and "include"), or "containing" (and any forms of containing, such as "contains" and "contain") are inclusive or open-ended, and do not exclude additional, unrecited elements or method steps.
[0034] The term "each independently selected from" means that when a group occurs more than once in a structure, the group can be independently selected at each occurrence.
[0035] The term "polymer" refers to a compound comprising repeating structural units (monomers) connected by covalent chemical bonds. The polymer may be further derivatized, cross-linked, grafted or end-capped. Non-limiting examples of polymers include copolymers, terpolymers, tetrapolymers, quaternary polymers and homologues. The term "copolymer" refers to a copolymer obtained by polymerizing a polymer consisting essentially of two or more different types of monomers.
[0036] The term "mucoadhesive" refers to an adhesive that adheres or sticks to the skin or mucus or mucosal cells or tooth surfaces.
[0037] As used herein, "denture" means a partial or complete upper or lower denture, or all of the above. Ideally, the composition should function as an effective means of isolating, cushioning, and securely positioning the denture. The composition should maintain its characteristics and properties in powder and paste forms during storage under a variety of climatic conditions such as temperature and humidity; be able to be quickly and easily applied to the denture surface; not cause irritation or discomfort to the user; be safe and non-toxic; have no unpleasant odor or color; have no unpalatable taste; provide antiseptic and bactericidal properties to prevent or inhibit the growth of organisms commonly found in the oral cavity; and function as a deodorant or an agent to prevent the putrefaction or malodorous decomposition of food secretions trapped under or near the denture.
[0038] As used herein, "alkyl vinyl ether copolymer" refers to a predetermined weight average molecular weight of about 500,000 to 3,000,000, which is suitable for preparing a denture adhesive by copolymerizing about 50 mole % maleic anhydride and about 50 mole % C1-C4 alkyl vinyl ether in a solvent or solventless process at about 50°C to 150°C in the presence of a free radical initiator to produce a uniform fine powder substantially free of residual maleic anhydride.
[0039] Alkyl vinyl ether maleic anhydride copolymers are obtained by copolymerizing alkyl vinyl ether monomers such as methyl vinyl ether, ethyl vinyl ether, divinyl ether, propyl vinyl ether and isobutyl vinyl ether with maleic anhydride to produce the corresponding alkyl vinyl ether-maleic anhydride copolymers, which are easily hydrolyzed to acid copolymers. Anhydride and acid forms are also available from commercial suppliers. For example, Ashland LLC offers polymerized free acid forms and corresponding anhydride forms under the "GANTREZ" trademark, "GANTREZ S Series" and "GANTREZ AN Series", respectively.
[0040] As used herein, "cellulose ether" refers to a cellulose derivative obtained by etherifying the hydroxyl group of cellulose using an etherifying agent. Useful cellulose ethers may be selected from methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydrophobically modified hydroxyalkyl cellulose, sodium carboxymethyl cellulose, and mixtures thereof.
[0041] The mucoadhesive composition including the denture adhesive composition of the present application comprises a metal salt of an alkyl vinyl ether-maleic acid / maleic anhydride copolymer, wherein the metal is selected from calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium and mixtures thereof.
[0042] The salt form of the methyl vinyl ether-maleic acid / maleic anhydride copolymer can be prepared by the interaction of the methyl vinyl ether-maleic acid / maleic anhydride copolymer or terpolymer with at least one inorganic salt of a metal such as calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium, and mixtures thereof. In one embodiment, sodium hydroxide or calcium hydroxide is used for the purposes of this application.
[0043] As used herein, "crosslinked" means that the composition contains intramolecular and / or intermolecular crosslinks, whether produced by covalent or non-covalent bonding. "Non-covalent" bonding includes hydrogen bonding and electrostatic (ionic) bonding.
[0044] According to one embodiment of the present application, a strongly swellable, moderately cross-linked PVP (polyvinyl pyrrolidone) polymer available from Ashland LLC under the trade name FlexiThixTM is used, which is obtained directly as a fine powder by precipitation polymerization of vinyl pyrrolidone in an organic solvent in the presence of a predetermined amount of a multifunctional cross-linking agent and a free radical initiator. The cross-linked PVP has a Brookfield viscosity of at least about 500 cps to about 50,000 cps in a 4% aqueous solution. The preferred viscosity range of the cross-linked PVP in the present application can be about 500 cps to about 50,000 cps, or about 800 cps to about 20,000 cps, or about 1000 cps to about 10,000 cps. The Brookfield viscosity can be measured at 2.5, 5, 10, 12, 20, 30 or 50 RPM and at 25°C.
[0045] Cross-linked PVP polymers useful in practicing the present application can be prepared according to U.S. Pat. No. 5,073,614 and U.S. Pat. No. 5,130,388, both issued to ISP Investments Inc. The teachings of these references are advantageously used for the purposes of the present application. In addition, these references are incorporated herein by reference in their entirety.
[0046] One element of the thickening additive composition according to the present application is a thickener comprising a strongly swelling, lightly to moderately crosslinked polyvinyl pyrrolidone as described in commonly owned US Pat. Nos. 5,312,619 and 5,139,770, the contents of which are incorporated herein by reference in their entirety. Unless otherwise indicated, the term "strongly swellable, lightly to moderately crosslinked PVP" specifically refers to a polymer consisting essentially of lightly to moderately crosslinked poly(N-vinyl-2-pyrrolidone) having at least one of the following non-limiting properties: (1) a water swelling parameter defined by its gel volume of from about 15 mL / g to about 300 mL / g, more particularly from about 15 mL / g to about 250 mL / g, and in other cases from about 15 mL / g to about 150 mL / g, or (2) a Brookfield viscosity of at least 2,000 cP, more particularly preferably at least about 5,000 cP, and in some cases at least about 10,000 cP, as measured at 25°C at 5% crosslinked PVP in a liquid carrier comprising water. References to these parameter ranges are provided in U.S. Pat. No. 5,073,614 (incorporated herein by reference) and Shih, JS et al. (1995). The synthesis methods of cross-linked PVP are disclosed in many references, including U.S. Pat. Nos. 5,073,614, 5,654,385 and 6,177,068, the contents of which are incorporated herein by reference. It will be appreciated by those skilled in the art that a variety of synthesis methods are possible, provided that the resulting polymer achieves at least one of the parameters defined above.
[0047] It is contemplated that any other possible polymerization method known to those skilled in the art can be used that can provide such strongly swollen, moderately cross-linked fine white powder PVP. Such polymerization methods may include, but are not limited to, precipitation polymerization, inverse emulsion polymerization, gel polymerization, dispersion polymerization, solution polymerization, emulsion polymerization, bulk polymerization, suspension polymerization, liquid dispersion polymerization (LDP) and ionic polymerization.
[0048] Other preferred polymerization techniques for preparing the polymers of the present application are disclosed in (1) Wiley, "Principles of Polymerization", 4th edition, 2004 by George Odian, and (2) WO2012061147A1 assigned to ISP Investments Inc., the disclosures of which are incorporated herein by reference. In addition, the polymerization of polymers that can be used in the practice of the present application may optionally require suitable catalysts or initiators, stabilizers, salts, pH adjusters, dispersants, thickeners, solvents, acidic agents, alkaline agents and / or photoinitiators depending on the type of polymerization technique employed. Those skilled in the art can easily obtain such information from relevant literature known in the art or from Wiley, "Principles of Polymerization", 4th edition, 2004 by George Odian, which is incorporated herein by reference in its entirety.
[0049] In one embodiment, the polymer is poly-N-vinyl-poly-2-pyrrolidone. Poly-N-vinyl-poly-2-pyrrolidone is also commonly referred to as polyvinyl pyrrolidone or "PVP". PVP refers to a polymer comprising vinyl pyrrolidone (also known as N-vinyl pyrrolidone, N-vinyl-2-pyrrolidone and N-vinyl-2-pyrrolidone) as a monomer unit. Suitable vinyl pyrrolidone polymers include poly (-vinyl-pyrrolidone) (PVP) and S-630, K-90, K-120.
[0050] Cross-linked polyvinylpyrrolidone is commercially available, for example, as HYDROGEN® from BASF. Type CL or from Ashland LLC XL and FlexithixTM PVP.
[0051] Cross-linked polyvinylpyrrolidone is used as a tablet disintegrant primarily in relatively crude form (Kollidon CL in the 120 micron range, Polyplasdone XL in the 130 micron range) with an average particle size of more than 100 microns.
[0052] In another embodiment, the present application relates to a swellable cross-linked PVP polymer that can be swelled in an organic solvent (preferably an aliphatic hydrocarbon, such as a C3-C 10 The present invention is directly prepared in the form of fine white powder by precipitation polymerization of vinyl pyrrolidone in a saturated, branched or unbranched, cyclic or acyclic aliphatic hydrocarbon, most preferably cyclohexane or heptane, or a mixture thereof, in the presence of a predetermined amount of a crosslinking agent and a free radical polymerization initiator.
[0053] In various embodiments of the present application, crosslinked polymers of vinyl pyrrolidone (including copolymers of vinyl pyrrolidone and other monomeric materials) which are porous granular or beaded even when wetted and swollen are produced by polymerizing the monomeric material with a controlled amount of a crosslinking agent in an aqueous solution of an electrolyte to form an insoluble polymer, and the excess monomer is kept in suspension by mechanical stirring.
[0054] In various embodiments of the present invention, the crosslinked vinyl pyrrolidone polymer maintains particulate form even when swollen by a liquid and comprises a porous granular or beaded vinyl pyrrolidone polymer and one or more copolymerizable monomers. To prepare the shape-retaining, porous, granular or beaded vinyl pyrrolidone polymer, the monomer material and at least a critical amount of a crosslinking agent are mechanically maintained in suspension in an aqueous solution of an electrolyte during a free radical polymerization process.
[0055] In one embodiment, the present application uses a strongly swellable, moderately cross-linked PVP polymer obtained directly as a fine powder by precipitation polymerizing vinyl pyrrolidone in an organic solvent in the presence of a predetermined amount of a multifunctional cross-linking agent and a free radical initiator.
[0056] In another embodiment, the present application employs a strongly swelling, moderately cross-linked PVP polymer-based fine powder characterized by a hydrogel volume of about 15 ml / g to 150 ml / g of polymer and a Brookfield viscosity of at least 1000 cps to 10,000 cps in a 5% aqueous solution.
[0057] According to various embodiments of the present application, copolymers of methyl vinyl ether and maleic anhydride in a certain molecular weight range are commercially available under the trade name (Ashland). Specifically, AN is a preferred copolymer. Other available Copolymers include S provides free acid form AN, to Provided by MS S mixed salt of sodium and calcium, and ES provides Half ester derivative of S.
[0058] According to one embodiment of the present application, a crosslinked methyl vinyl ether / maleic anhydride copolymer Stabileze QM is used. Preferably, a 1,9-decadiene crosslinked copolymer, such as Stabileze QM-PVM / MA copolymer commercially available from Ashland LLC. The amount of the crosslinking agent is generally about 1 mol % to about 5 mol % based on the monovinyl alkyl ether. Examples of suitable crosslinking agents include divinyl ethers of aliphatic diols, such as divinyl ethers of 1,2-ethanediol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, and 1,12-dodecanediol, and divinyl ethers of diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, hexaethylene glycol, heptaethylene glycol, octaethylene glycol, nonaethylene glycol, decaethylene glycol, and polyalkylene glycols having a molecular weight of up to about 5900. Other suitable crosslinking agents include 1,7-octadiene; 1,9-decadiene; divinylbenzene; N,N'-bis-methylene acrylamide; acrylates such as polyethylene glycol diacrylate, trimethylolpropane triacrylate, propylene glycol diacrylate; polyols esterified once or twice with triallylamine acrylate, tetraallylethylenediamine, diallyl phthalate, and the like.
[0059] The present application comprises an orally acceptable carrier or vehicle which preferably comprises a hydrophobic (oil) or hydrophilic (non-oil) component.
[0060] The hydrophobic oil or hydrophilic non-oil component of the present application can be selected from: liquid petrolatum, petrolatum, mineral oil, glycerin, natural and synthetic oils, fats, silicones and silicone derivatives, polyvinyl acetate, polyethylene glycol, propylene glycol, polypropylene glycol, poly(ethylene oxide-propylene oxide) copolymers, diethylene glycol, triethylene glycol, sorbitol, water, orally acceptable surfactants and mixtures thereof; natural and synthetic waxes such as animal waxes such as beeswax, lanolin and shellac; hydrocarbons; hydrocarbon derivatives; vegetable oil waxes such as carnauba wax, candela and bayberry wax; vegetable oils such as caprylic / capric triglyceride; vegetable oils such as corn oil, sunflower oil, soybean oil, castor oil, palm oil, coconut oil, olive oil and rapeseed oil or mixtures thereof; and animal oils such as fish oil and oleic acid, and mixtures thereof.
[0061] In another embodiment, the present application discloses the preparation of mucoadhesive oral compositions and the use of such formulations to sustain the release of active ingredients selected from, but not limited to, antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, and sweeteners.
[0062] The antibacterial compound of the present application can be selected from: halogenated diphenyl ethers (such as triclosan), herbal extracts and essential oils (such as rosemary extract, tea extract, magnolia extract, thymol, menthol, eucalyptol, geraniol, carvacrol, citral, hinokitiol, catechol, methyl salicylate, epicatechin gallate, epicatechin, gallic acid, miswak extract, sea buckthorn extract), biguanide antibacterial agents (such as chlorhexidine, alexidin or octenidine), quaternary ammonium compounds (such as cetylpyridinium chloride (CPC), benzyl alcohol, ...
[0063] The invention also includes the following: antibacterial agents: salifluor, tin salts, stannous fluoride, sodium fluoride, potassium fluoride, sodium monofluorophosphate, sodium fluorosilicate, ammonium fluorosilicate, amine fluoride, and ammonium fluoride. The anti-inflammatory compound of the present application can be selected from but not limited to: triamcinolone acetonide (trade name: Kenalog), fluocinolone acetonide (trade name: Vanos), dexamethasone (trade name: decadron), herpes, aphthasol, ketorolac, flurbiprofen, ibuprofen, naproxen, indomethacin, aspirin, ketoprofen, piroxicam and meclofenamic acid.
[0063] The pain relieving compound of the present application can be selected from, but not limited to, benzocaine, lidocaine, procaine, prilocaine, mepivacaine, aspirin, ibuprofen, diclofenac and methyl salicylate.
[0064] The antioxidant compounds of the present application can be selected from, but are not limited to, vitamin E, ascorbic acid, uric acid, carotenoids, vitamin A, flavonoids, polyphenols, herbal antioxidants, melatonin, aminoindoles, lipoic acid, caffeic acid, beta-carotene, ellagic acid, epicatechin, epicatechin gallate, ferulic acid, genistein, kojic acid, alpha-lipoic acid, lycopene, resveratrol, resorcinol, rosmarinic acid, silybin, theaflavins, tocopherols, tocotrienols, trolox and ubiquinone-10.
[0065] The enzyme of the present application can be selected from but not limited to: protease: papain, bromelain, chymotrypsin, ficin and alkaline protease; carbohydrase: glucoamylase, α-amylase, β-amylase, glucanase and deformable enzyme; lipase: plant lipase, gastric lipase and pancreatic lipase; and glucoamylase, saccharifying glucoamylase derived from Aspergillus niger.
[0066] The flavoring agent of the present application can be selected from, but not limited to, essential oils and various flavoring aldehydes, esters, and alcohols. Examples of essential oils include spearmint, mint, wintergreen, sassafras, cloves, sage, eucalyptus, marjoram, cinnamon, carvone, anethole, oils of lemon, lime, grapefruit, and orange, wild oregano oil, tea tree leaf oil, wintergreen oil, coconut oil, myrrh oil, and grapefruit peel oil.
[0067] The cooling agent of the present application can be selected from but not limited to: menthol, menthyl lactate, menthyl monosuccinate, ethylene glycol carbonate, propylene glycol carbonate, menthone glycerol ketal, 3-(l-menthoxy)propane-1,2-diol, (-)-isopulegol, WS-3 [N-ethyl-p-menthane-3-carboxamide], WS-23 (2-isopropyl-N,2,3-trimethylbutyramide), WS-5 [3-(p-menthane-3-carboxamido)ethyl acetate].
[0068] The cooling agent of the present application can be selected from, but not limited to, acesulfame potassium, aspartame, neotame, saccharin, sucralose, stevia, Advantame, cyclamate, sorbitol, xylitol and erythritol.
[0069] In some embodiments, based on the total weight of the mucoadhesive composition including the denture adhesive composition of the present application, the copolymer of alkyl vinyl ether-maleic acid / maleic anhydride or its salt is a suitable amount ranging from about 10 wt % to about 20 wt %, or from about 20 wt % to about 30 wt %, or from about 30 wt % to about 40 wt %, or from about 40 wt % to about 50 wt %, or from about 50 wt % to about 60 wt %, or from about 60 wt % to about 75 wt %.
[0070] In some embodiments, the cellulose ether is used in an amount ranging from about 10 wt % to about 20 wt %, or from about 20 wt % to about 30 wt %, or from about 30 wt % to about 40 wt %, or from about 40 wt % to about 50 wt %, based on the total weight of the mucoadhesive composition including the denture adhesive composition of the present application.
[0071] In some embodiments, the cross-linked PVP is present in a suitable amount ranging from about 0.1 wt % to about 1 wt %, or from about 0.1 wt % to about 5 wt %, or from about 5 wt % to about 10 wt %, based on the total weight of the mucoadhesive composition including the denture adhesive composition.
[0072] In some embodiments of the present application, based on the total weight of the mucoadhesive composition including the denture adhesive composition, the cross-linked methyl vinyl ether / maleic anhydride (e.g., Stabilize TMQM), or cross-linked methyl vinyl ether / maleic acid or its salt is a suitable amount in the range of about 0.1 wt % to about 1 wt %, or about 1 wt % to about 5 wt %, or about 5 wt % to about 10 wt %.
[0073] In some embodiments, the carrier based on the hydrophobic oil or hydrophilic non-oil component is a suitable amount ranging from about 10 wt % to about 20 wt %, or from about 20 wt % to about 30 wt %, or from about 30 wt % to about 40 wt %, or from about 40 wt % to about 50 wt %, or from about 50 wt % to about 60 wt %, or from about 60 wt % to about 75 wt %, based on the total weight of the mucoadhesive composition including the denture adhesive composition.
[0074] In some embodiments, antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, and sweeteners are suitable amounts ranging from about 0.01 wt % to about 0.1 wt %, or from about 0.1 wt % to about 1 wt %, or from about 1 wt % to about 10 wt %, or from about 10 wt % to about 20 wt %, based on the total weight of the mucoadhesive composition including the denture adhesive composition.
[0075] In some embodiments, the alkyl vinyl ether-maleic acid / anhydride copolymer present in the composition of the present application has a weight average molecular weight of about 500,000 to 3,000,000, which is suitable for preparing a denture adhesive by copolymerizing about 50 mol% of maleic anhydride and about 50 mol% of C1-C4 alkyl vinyl ether in a solvent or solventless process at about 50° C. to 150° C. in the presence of a free radical initiator to produce a uniform fine powder substantially free of residual maleic acid copolymer or maleic anhydride copolymer. The copolymer of maleic anhydride and C1-C4 alkyl vinyl ether preferably has a Brookfield viscosity of about 50,000 cps to about 150,000 cps.
[0076] In some embodiments, the methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer (PVM / MA copolymer) present in the composition of the present application has a number average molecular weight of about 50,000 to about 500,000 Daltons, wherein about 50% by weight to about 100% by weight of the carboxyl units in the polymer are converted to a mixture of metal salts, further wherein the metal is selected from calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium and mixtures thereof.
[0077] In some embodiments, the salt of the copolymer of alkyl vinyl ether-maleic acid or the salt of the copolymer of alkyl vinyl ether-maleic anhydride has a specific viscosity of 2.5 to 5.0 when measured as a 1 weight / volume % solution in methyl ethyl ketone (MEK) solution at 25°C.
[0078] As disclosed herein, in some embodiments, the weight average molecular weight (Mw) of methyl vinyl ether ranges from about 700,000 to about 3,000,000. In some embodiments, the weight average molecular weight (Mw) of methyl vinyl ether copolymers ranges from 500,000 to 3,000,000.
[0079] As disclosed herein, in some embodiments, the number average molecular weight of the methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer or salts thereof (PVM / MA copolymer) ranges from 50,000 to about 500,000.
[0080] As disclosed herein, in some embodiments, the molecular weight of sodium carboxymethylcellulose is from about 500,000 to about 1,200,000 Daltons. In some embodiments, the molecular weight of sodium carboxymethylcellulose ranges from 600,000 to about 800,000 Daltons.
[0081] According to another embodiment of the application, it is contemplated to use at least one excipient. Suitable excipients for the purpose of the application are selected from preservatives, flavoring agents, coloring agents, sweeteners, plasticizers, binders, thickeners, carriers, coloring agents, carriers, flavoring agents, spices, sensory agents (sensate) and mixtures thereof.
[0082] In one embodiment, the mucoadhesive composition is an oral gel, oral ointment, mouthwash, oral rinse, oral buccal composition, sublingual composition, palatal composition, and denture adhesive composition in the form of a dentifrice, denture cleanser, chewing gum, lozenge, mouth spray, mousse, foam, dental appliance (dental floss or dental tape), dental solution, denture cleanser, toothpaste, tooth powder, topical oral gel, mouthwash, mouth spray, denture product, dissolvable film, strip, oral tablet, aerosol, wafer, chewing gum, or breath freshener.
[0083] In one embodiment, it is contemplated that materials suitable for use in mucoadhesive compositions including denture adhesives are safe and palatable, particularly at relevant concentrations for use in hygienic compositions such as liquids, powders, pastes, gels, thermoplastic solids, hydrogels, or combinations thereof.
[0084] The purpose of providing the following examples is to illustrate but not to limit the preparation and use of polymers. In these examples, the following abbreviations are used:
[0085] PVP: Polyvinylpyrrolidone
[0086] MVE : Methyl Vinyl Ether
[0087] MA :Maleic anhydride / maleic acid
[0088] CMC: Carboxymethyl cellulose
[0089] wt% : weight percentage
[0090] Flexithix: lightly to moderately cross-linked polyvinyl pyrrolidone
[0091] Polyplasdone XL-10: Self-crosslinked polyvinylpyrrolidone
[0092] Stabilieze QM: Poly(methyl vinyl ether / maleic anhydride) cross-linked with 1,9-decadiene
[0093] PVP K-90: Polyvinylpyrrolidone powder with an average molecular weight of 1,300,000 Daltons
[0094] Gantrez MS-955: Poly(methyl vinyl ether / maleic anhydride) sodium / calcium mixed salt
[0095] Aqualon CMC 7H3SXF : Sodium carboxymethyl cellulose
[0096] Germaben II: a liquid containing propylene glycol, propylparaben, methylparaben, and diazolidinyl urea
[0097] PVP K-15: Polyvinylpyrrolidone powder with an average molecular weight of 8,000 Daltons
[0098] In addition, some aspects of the present application are described in detail by the following examples. The examples given here are used to illustrate the present application and are not intended to limit it.
[0099] Example
[0100] Performance enhancer materials useful in the present invention are hydrophilic polymers that are swellable or partially soluble in water / saliva. These polymers can be characterized by the remarkable affinity of their chemical structure for aqueous solutions in which they swell rather than dissolve. The absorption of these polymers ranges from low to moderate, typically retaining 1 wt% to 30 wt% of water within their structure. Superabsorbent polymers that can retain more than 30 wt% of their weight in water cannot be used in this application because they tend to destabilize the denture adhesive paste by absorbing excess saliva that promotes exudation.
[0101] Table 1: Performance Enhancers and Adhesive Polymers
[0102]
[0103] Comparative Example 1: Standard oil-based denture adhesive formulation (E1)
[0104] A 200 g batch of a standard oil-based denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a digitally controlled thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 194°F (90°C). The ingredients required to make the denture adhesive paste were added according to Table 1. Petrolatum (40 g) and white mineral oil (40 g) were charged to the heating bowl of the KitchenAid mixer and mixed at low speed for 10 minutes until the petrolatum was completely melted and a homogenous transparent liquid was produced. Sodium carboxymethylcellulose (54 g) was added to the KitchenAid and mixed vigorously with the oil for 30 minutes until uniformly dispersed. The Ca / Na mixed salt of poly(MVE / MA) (66 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. The appropriate pigment was added and mixed until uniformly dispersed. The heat was turned off and the denture adhesive paste was allowed to cool to room temperature by continuous stirring at medium speed for 2 hours. After cooling to room temperature, 50 g of the denture adhesive sample was filled into appropriate dispensing tubes and heat sealed. The remaining denture adhesive was filled into clear glass jars for storage stability studies.
[0105] Example 2: Experimental oil-based denture adhesive formulation (E12) 5% PVP K-90
[0106] A 200 g batch of the experimental oil-based denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a digitally controlled thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 194°F (90°C). The ingredients required to make the denture adhesive paste were added according to Table 1. Petrolatum (40 g) and white mineral oil (40 g) were placed in the heating bowl of the KitchenAid mixer and mixed at low speed for 10 minutes until the petrolatum was completely melted and a homogeneous transparent liquid was produced. Uncross-linked PVP (PVP-K-90) (10 g) was added to the KitchenAid and mixed vigorously with the oil for 15 minutes until uniformly dispersed. Sodium carboxymethylcellulose (50 g) was added to the KitchenAid and mixed vigorously with the oil for 30 minutes until uniformly dispersed. The Ca / Na mixed salt of poly (MVE / MA) (60 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. Add the appropriate pigment and mix until uniformly dispersed. Turn off the heat and continue stirring at medium speed for 2 hours to allow the denture adhesive paste to cool to room temperature. After cooling to room temperature, fill 50g of the denture adhesive sample into an appropriate dispensing tube and heat seal it. The remaining denture adhesive is placed in a clear glass jar for storage stability studies.
[0107] Example 3: Experimental oil-based denture adhesive formulation (E13) 3% Stabileze QM
[0108] A 200 g batch of the experimental oil-based denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a digitally controlled thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 194°F (90°C). The ingredients required to make the denture adhesive paste were added according to Table 1. Petrolatum (40 g) and white mineral oil (40 g) were placed in the heating bowl of the KitchenAid mixer and mixed at low speed for 10 minutes until the petrolatum was completely melted and a homogeneous transparent liquid was produced. Cross-linked poly (MVE / MA) (6 g) was added to the KitchenAid and mixed vigorously with the oil for 15 minutes until uniformly dispersed. Sodium carboxymethyl cellulose (50 g) was added to the KitchenAid and mixed vigorously with the oil for 30 minutes until uniformly dispersed. The Ca / Na mixed salt of poly (MVE / MA) (64 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. Add the appropriate pigment and mix until uniformly dispersed. Turn off the heat and continue stirring at medium speed for 2 hours to allow the denture adhesive paste to cool to room temperature. After cooling to room temperature, fill 50g of the denture adhesive sample into an appropriate dispensing tube and heat seal it. The remaining denture adhesive is placed in a clear glass jar for storage stability studies.
[0109] Example 4: Experimental oil-based denture adhesive formulation (E14) 3% Polyplasdone XL-10
[0110] A 200 g batch of the experimental oil-based denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a CNC thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 194°F (90°C). The ingredients required to make the denture adhesive paste were added according to Table 1. Petrolatum (40 g) and white mineral oil (40 g) were placed in the heating bowl of the KitchenAid mixer and mixed at low speed for 10 minutes until the petrolatum was completely melted and a homogeneous transparent liquid was produced. Cross-linked PVP Polyplasdone XL-10 (6 g) was added to the KitchenAid and mixed vigorously with the oil for 15 minutes until uniformly dispersed. Sodium carboxymethylcellulose (50 g) was added to the KitchenAid and mixed vigorously with the oil for 30 minutes until uniformly dispersed. The Ca / Na mixed salt of poly(MVE / MA) (64 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. Add appropriate pigments and mix until uniformly dispersed. Turn off the heat and continue stirring at medium speed for 2 hours to allow the denture adhesive paste to cool to room temperature. After cooling to room temperature, fill 50g of the denture adhesive sample into an appropriate dispensing tube and heat seal it. The remaining denture adhesive is placed in a clear glass jar for storage stability studies.
[0111] Example 5: Experimental oil-based denture adhesive formulation (E15) 3% Flexithix
[0112] A 200 g batch of the experimental oil-based denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a CNC thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 194°F (90°C). The ingredients required to make the denture adhesive paste were added according to Table 1. Petrolatum (40 g) and white mineral oil (40 g) were placed in the heating bowl of the KitchenAid mixer and mixed at low speed for 10 minutes until the petrolatum was completely melted and a homogeneous transparent liquid was produced. Cross-linked PVP, Flexithix (6 g) was added to the KitchenAid and mixed vigorously with the oil for 15 minutes until uniformly dispersed. Sodium carboxymethylcellulose (50 g) was added to the KitchenAid and mixed vigorously with the oil for 30 minutes until uniformly dispersed. The Ca / Na mixed salt of poly(MVE / MA) (64 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. Add the appropriate pigment and mix until uniformly dispersed. Turn off the heat and continue stirring at medium speed for 2 hours to allow the denture adhesive paste to cool to room temperature. After cooling to room temperature, fill 50g of the denture adhesive sample into an appropriate dispensing tube and heat seal it. The remaining denture adhesive is placed in a clear glass jar for storage stability studies.
[0113] Example 6: Experimental oil-based denture adhesive formulation (E16) 2.5% Polyplasdone XL-10 + 2.5% Flexithix
[0114] A 200 g batch of the experimental oil-based denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a digitally controlled thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 194°F (90°C). The ingredients required to make the denture adhesive paste were added according to Table 1. Petrolatum (40 g) and white mineral oil (40 g) were charged to the heating bowl of the KitchenAid mixer and mixed at low speed for 10 minutes until the petrolatum was completely melted and a homogenous transparent liquid was produced. Cross-linked PVP, Polyplasdone XL-10 (5 g) and Flexithix (5 g) were added to the KitchenAid and mixed vigorously with the oil for 15 minutes until uniformly dispersed. Sodium carboxymethylcellulose (50 g) was added to the KitchenAid and mixed vigorously with the oil for 30 minutes until uniformly dispersed. The Ca / Na mixed salt of poly(MVE / MA) (60 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. Add the appropriate pigment and mix until evenly dispersed. Turn off the heat and continue stirring at medium speed for 2 hours to allow the denture adhesive paste to cool to room temperature. After cooling to room temperature, fill 50g of the denture adhesive sample into an appropriate dispensing tube and heat seal it. The remaining denture adhesive is placed in a clear glass jar for storage stability studies.
[0115] Example 7: Experimental Oil-Free Denture Adhesive Formulation (OF1) 1% PVP K-15
[0116] A 200 g batch of a standard oil-free denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a digitally controlled thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 115°F (~46°C). The ingredients required to make the denture adhesive paste were added according to Table 2. Propylene glycol (38.5 g) and PEG-400 (38.5 g) were added to the heating bowl of the KitchenAid mixer and mixed at low speed for 20 minutes until a homogeneous transparent liquid was obtained. PVP K-15 (2 g) was added to the KitchenAid mixer and mixed at high speed for 45 minutes until a clear solution was obtained. Sodium carboxymethylcellulose (54 g) was then added to the KitchenAid and mixed vigorously for 30 minutes until uniformly dispersed. The Ca / Na mixed salt of poly(MVE / MA) (66 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. Germaben II preservative (1 g) was then added and mixed for another 15 minutes. Turn off the heat and continue stirring at medium speed for 2 hours to allow the denture adhesive paste to cool to room temperature. After cooling to room temperature, fill 50g of the denture adhesive sample into an appropriate dispensing tube and heat seal it. The remaining denture adhesive is placed in a clear glass jar for storage stability studies.
[0117] Example 8: Experimental Oil-Free Denture Adhesive Formulation (OF2) 1% Flexithix
[0118] A 200 g batch of a standard oil-free denture adhesive formulation was prepared in a KitchenAid planetary mixer equipped with a CNC thermostatic heating jacket. The heating jacket was set to maintain a constant temperature of 115°F (~46°C). The ingredients required to make the denture adhesive paste were added according to Table 2. Propylene glycol (39.5 g) and PEG-400 (39.5 g) were added to the heated bowl of the KitchenAid mixer and mixed at low speed for 20 minutes until a homogeneous, transparent liquid was obtained. Cross-linked PVP, Flexithix (2 g) was added to the KitchenAid mixer and mixed at high speed for 45 minutes until a clear, thin gel was obtained. Sodium carboxymethylcellulose (54 g) was then added to the KitchenAid and mixed vigorously for 30 minutes until uniformly dispersed. The mixed Ca / Na salt of poly(MVE / MA) (66 g) was then added to the KitchenAid and mixed at medium speed for another 30 minutes to produce a paste of uniform consistency. Germaben II preservative (1 g) was then added and mixed for another 15 minutes. Turn off the heat and continue stirring at medium speed for 2 hours to allow the denture adhesive paste to cool to room temperature. After cooling to room temperature, 50 g of the denture adhesive sample was filled into an appropriate dispensing tube and heat sealed. The remaining denture adhesive was filled into a clear glass jar for storage stability studies.
[0119] Table 2: Oil-based denture adhesive composition
[0120]
[0121] Example 9: Testing Methods for Denture Adhesives
[0122] Adhesion force and relative film thickness of denture adhesive were recorded on a TA.XT Plus texture analyzer instrument from Stable Microsystems TextureTechnologies Corp., equipped with a 50 Kg load cell and connected to a PC running Exponent software version 6.1.11.0. The texture analyzer was equipped with a custom denture-shaped plexiglass probe-clamp assembly. Artificial saliva irrigation between the walls of the plexiglass probe-clamp assembly was achieved using a peristaltic pump. Real-time time-lapse images of denture adhesive pastes evaluated for adhesion performance on the texture analyzer instrument were recorded using a Canon EOS 5d Mark IV digital SLR camera.
[0123] The sample tube containing the denture adhesive paste was purged of trapped air and, with the cap in place, squeezed several times to homogenize the contents of the tube. Always discard the first 100 mg of material that comes out of the tube.
[0124] On an analytical balance, three nearly identical strips of denture adhesive paste were weighed into the denture-shaped cavity of the bottom plexiglass fixture. For each test, the total mass of denture adhesive paste applied to the bottom fixture was 2.0 (+ 0.1) g. The bottom fixture was mounted on the texture analyzer instrument and the top probe was moved down into the cavity of the bottom fixture to evenly apply the denture adhesive paste and fill the lower half of the cavity under a precise compression force of 4.5 Kg. Begin pouring artificial saliva. Throughout the experiment, the denture adhesive paste remained in contact and immersed in a thin layer of artificial saliva that was continuously renewed at a flow rate of 1 ml / min. Once the denture adhesive paste layer was completely covered with artificial saliva, the 7-hour test procedure began. The adhesion force (in Newtons) during chewing and the film thickness (in mm) of the denture adhesive between the top and bottom probes were continuously measured during the experiment. Four consecutive tests were performed on each sample of the prepared denture adhesive formulation. For adhesion performance and thickness variation, the average curves of 4 tests for each sample were compared. The total adhesion for each sample was calculated as the area under the average curve of 4 consecutive tests for each sample.
[0125] Table 3: Oil-free denture adhesive composition
[0126]
[0127]
[0128] Example 10: Adhesion Results
[0129] Figure 1-4 Represents the overlap of the average adhesion spectra of sample oil-based denture adhesives E1, E12-16. The adhesion spectrum trace for each denture adhesive sample is the average of four consecutive tests. Each overlapping curve is divided into alternating phases of slow chewing movement or rest phase (RP) and fast chewing movement or dynamic chewing (DM). The adhesion force is recorded and reported in Newtons (N). Figure 5 The total adhesion force for each representative denture adhesive formulation is shown. The total adhesion force (in N) was measured as the total area under the mean adhesion curve trace for each representative denture adhesive formulation.
[0130] Figure 6 Represents the overlap of the average adhesion spectra of samples oil-free denture adhesives OF1 and OF2. The adhesion force spectrum trace for each denture adhesive sample is the average of four consecutive tests. Each overlapping curve is divided into alternating phases of slow chewing movement or rest phase (RP) and fast chewing movement or dynamic chewing (DM). The adhesion force is recorded and reported in Newtons (N). Figure 7 The total adhesion force for each representative oil-free denture adhesive formulation is shown. The total adhesion force (in N) was measured as the total area under the mean adhesion curve trace for each representative denture adhesive formulation.
[0131] Example 11: Stability of Denture Adhesive Formulations
[0132] Figure 8 The stability of selected oil-based denture adhesive formulations after storage at 45°C for 12 weeks is shown. The degree of syneresis of the hydrophobic carrier in the formulation after storage at 45°C for 12 weeks is regarded as oil separation, calculated as the % of the height of the formulation separated as oil due to syneresis, and is considered a measure of formulation stability. The lower the % oil separation, the better the stability of the sample after storage at 45°C for 12 weeks.
[0133] Example 12: Mucoadhesive formulation
[0134] Examples of orally acceptable mucoadhesive formulations are described in Tables 4 and 5.
[0135] Table 4: Oil-based mucoadhesive composition
[0136]
[0137]
[0138] Table 5: Oil-free mucoadhesive composition
[0139]
[0140] Although the compositions and methods of the disclosed and / or claimed inventive concepts have been described in terms of specific aspects, it will be apparent to those skilled in the art that changes may be made to the compositions and / or methods and the steps or sequence of steps of the methods described herein without departing from the concept, spirit and scope of the disclosed and / or claimed inventive concepts, and all such similar substitutes and modifications.
Claims
1. A denture adhesive composition comprising: i. 10 wt % to 75 wt % of a maleic acid copolymer or a maleic anhydride copolymer or a salt thereof; ii. 10 to 50 wt. % of at least one cellulose ether; iii. 0.1 wt % to 10 wt % of a swellable but water-insoluble cross-linked polyvinylpyrrolidone polymer; and iv. 30% to 70% by weight of an orally acceptable carrier.
2. The denture adhesive composition according to claim 1, wherein The maleic acid copolymer or maleic anhydride copolymer comprises repeating units of maleic acid or maleic anhydride or a salt thereof.
3. The denture adhesive composition according to claim 1, wherein The maleic acid copolymer or maleic anhydride copolymer comprises maleic acid or maleic anhydride and C1-C4 alkyl vinyl ether, has a predetermined weight average molecular weight of 500,000 to 3,000,000, and is prepared by: in a solvent or solvent-free process, at 50° C. to 150° C., in the presence of a free radical initiator, reacting 50 mol % of maleic acid or maleic anhydride, 50 mol % of C1-C4 alkyl vinyl ether, 1-4 The alkyl vinyl ether is copolymerized to produce a uniform fine powder substantially free of residual maleic anhydride.
4. The denture adhesive composition according to claim 3, wherein: The number average molecular weight of the methyl vinyl ether-maleic acid copolymer or the methyl vinyl ether-maleic anhydride copolymer is 50,000 to 500,000, wherein 50% to 100% by weight of the carboxyl units in the polymer are converted into a mixture of metal salts, the metal being selected from calcium, sodium, strontium, zinc, magnesium, iron, boron, aluminum, potassium, vanadium, chromium, manganese, nickel, copper, yttrium, titanium and mixtures thereof.
5. The denture adhesive composition according to claim 4, wherein The methyl vinyl ether-maleic acid copolymer or the salt of the methyl vinyl ether-maleic anhydride copolymer has a specific viscosity of 2.5 to 5.0 when measured as a 1 weight / volume % solution in a methyl ethyl ketone (MEK) solution at 25°C.
6. The denture adhesive composition according to claim 5, wherein: The methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer or a salt thereof constitutes 18 to 66 weight % of the composition.
7. The denture adhesive composition according to claim 6, wherein: The weight average molecular weight of the methyl vinyl ether-maleic acid copolymer or the methyl vinyl ether-anhydride copolymer is 700,000 to 3,000,000.
8. The denture adhesive composition according to claim 1, wherein The cellulose ether is selected from methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, sodium carboxymethyl cellulose and mixtures thereof.
9. The denture adhesive composition according to claim 8, wherein: The cellulose ether is sodium carboxymethyl cellulose (NaCMC).
10. The denture adhesive composition according to claim 9, wherein: The carboxymethyl cellulose has a number average molecular weight ranging from 500,000 to 1,200,000 Daltons.
11. The denture adhesive composition according to claim 10, wherein: The number average molecular weight of the sodium carboxymethyl cellulose ranges from 600,000 to 800,000 Daltons.
12. The denture adhesive composition according to claim 11, wherein The sodium carboxymethylcellulose constitutes 15% to 50% by weight of the denture adhesive composition.
13. The denture adhesive composition according to claim 1, wherein: The cross-linked polyvinylpyrrolidone is in the form of a fine, free-flowing white powder.
14. The denture adhesive composition according to claim 1, further comprising 0.001 wt % to 5 wt % of an excipient, wherein the excipient is selected from the group consisting of preservatives, colorants, sweeteners, pigments, plasticizers, binders, thickeners, carriers, buffers, humectants, surfactants, detergents, foaming agents, gelling agents, stabilizers, abrasives, antioxidant carriers, desensitizers, flavors, sensates, and mixtures thereof.
15. The denture adhesive composition of claim 1, further comprising 0.01 wt% to 20 wt% of an active ingredient selected from antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, sweeteners, and mixtures thereof.
16. The denture adhesive composition according to claim 1, wherein: The orally acceptable carrier comprises a hydrophobic oil or a hydrophilic non-oil component selected from petrolatum, mineral oil, olive oil, vegetable oil, silicone or glycerin, polyethylene glycol, propylene glycol, poly(ethylene oxide-propylene oxide) copolymer, diethylene glycol, triethylene glycol, sorbitol, water, an orally acceptable surfactant and a mixture thereof.
17. The denture adhesive composition according to claim 1, wherein: The denture adhesive composition is in the form of a powder, cream, paste, liquid, gel, aerosol and / or sheet.
18. A denture adhesive oral composition comprising: i. 15 wt % to 70 wt % of a maleic acid copolymer selected from methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer or a salt thereof; ii. 10% to 50% by weight of at least one carboxymethyl cellulose; iii. 0.1 wt % to 10 wt % of swellable, water-insoluble cross-linked polyvinylpyrrolidone; iv. 10% to 60% by weight of an orally acceptable carrier; and v. 0.01 wt % to 20 wt % of an active ingredient selected from antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, sweeteners, and mixtures thereof, and further wherein the composition is a gel or a liquid.
19. A denture adhesive composition comprising: i. 15 wt % to 70 wt % of a maleic acid copolymer selected from methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer or a salt thereof; ii. 10% to 50% by weight of at least one carboxymethyl cellulose; iii. 0.1 wt % to 10 wt % of swellable, water-insoluble cross-linked polyvinylpyrrolidone; iv. 10% to 60% by weight of an orally acceptable carrier; and v. 0.01 wt % to 20 wt % of an active ingredient selected from antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, sweeteners, and mixtures thereof, and further wherein the composition is a gel or a liquid.
20. The denture adhesive composition according to claim 19, wherein The composition is applied to the inner surface of the denture in an effective denture retaining amount.
21. The denture adhesive composition according to claim 19, wherein The composition is used to improve denture adhesion properties, including strength and duration of adhesion retention, film thickness, buffering effect, exudation control, shelf-life storage stability, easy cleaning, extended retention time and adhesion enhancement properties.
22. Use of a denture adhesive composition in the preparation of an agent for adhering a denture having a biological contact surface to a gum or roof of the mouth, the denture adhesive composition comprising: i. 15 wt % to 70 wt % of a maleic acid copolymer selected from methyl vinyl ether-maleic acid copolymer or methyl vinyl ether-maleic anhydride copolymer or a salt thereof; ii. 10% to 50% by weight of at least one carboxymethyl cellulose; iii. 0.1 wt % to 10 wt % of swellable, water-insoluble cross-linked polyvinylpyrrolidone; iv. 10% to 60% by weight of an orally acceptable carrier; and v. 0.01 wt % to 20 wt % of an active ingredient selected from antibacterial agents, anti-inflammatory agents, analgesics, antioxidants, enzymes, flavoring agents, cooling agents, sweeteners, and mixtures thereof.
Citation Information
Patent Citations
Denture adhesive hydrogel with dry tack
EP2620136B1
Cellulose-containing denture adhesive
US3440065A
Denture adhesive
US4569955A
Strongly swellable, moderately crosslinked polyvinylpyrrolidone
US5073614A
Precipitation polymerization process
US5130388A